Kinaray-a Online, Isang Love Story Inang Wika bilang Instagram ng Alaala at Huling Museo / Kinaray-a Online, A Love Story : Mother Tongue as an Instragram of Curated Memories. - Asenjo, Genevieve L. (Malay, 2015)
This is a preliminary valuation on the capacity and limitation of Mother Tongue, particularly of Kinaray-a, through the experience of Balay Sugidanun (House of Storytelling) as an online platform in the preservation and promotion of Mother Tongue via blogging, to dissemination in social media, for the possibility of forming new communities and alliances, in the time of Digital Humanities, Big Data, and Mother Tongue-based Multilingual Education (MTBLE) in the K to 12 program of the government.